Implementation of Pancasila Education in Preventing Radicalism in the Entikong Border Area West Kalimantan - Satriadi Galeh; Sapto Priyanto (Jurnal Studi Guru dan Pembelajaran, 2024)
This research aims to analyze or describe problems based on a literature review regarding the implementation of Pancasila education in preventing the development of acts of radicalism, in Entikong, West Kalimantan. The first step in this research is to study data from previous research, then collect primary data from books, journals and websites for data processing. After that, carry out data analysis with analysis stages; data reduction, data presentation (display), and verification or conclusions. Testing the validity of data in qualitative research includes testing internal validity (credibility), external validity (transferability), reliability (dependability), and objectivity (confirmability). The results of the research show that Pancasila is a very important part to study as a form of preventing the entry of radicalism in the world of Indonesian education. A Pancasila Education Implementation Strategy is needed in preventing the development of acts of radicalism in maintaining the integrity of the Indonesian nation with unity and oneness in uniting various kinds of differences, especially in the outermost regions of Indonesia that directly border other countries.